2020
DOI: 10.1088/1757-899x/980/1/012083
|View full text |Cite
|
Sign up to set email alerts
|

A review: The use of mangrove for biomonitoring on aquatic environment

Abstract: Mangroves have been investigated widely as plants that can absorb and accumulate heavy metals in their tissues. Due to that ability, mangroves have been used to reduce heavy metals in the aquatic environment. Furthermore, mangroves have been used for biomonitoring of heavy metals pollution. The use of mangroves for biomonitoring on aquatic environments has been considered as a cheap, rapid, and sufficient method. The mangrove is an organism that has the ability to absorb the contaminants of heavy metal and to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 46 publications
0
2
0
1
Order By: Relevance
“…Terjadinya pengurangan jumlah luasan ekosistem mangrove tentunya berdampak pada terjadinya penurunan kualitas kesehatan perairan pelabuhan Lembar dan sekitarnya, sedangkan mangrove sangat berperan penting dalam menopang kehidupan ekonomi dan kesehatan masyarakat pesisir, terutama terhadap cemaran logam berat yang berasal dari aktivitas pelabuhan Lembar. Hal ini didukung oleh berbagai studi terdahulu yang membuktikan bahwa mangrove merupakan salah satu bioakumulator logam berat berbahaya (Nur, 2013;Setiawan, 2013;Analuddin et al, 2017;Nilasari & Wibowo, 2018;Sasnita et al, 2017;Supriyantini et al, 2017;Warni et al, 2017;Khairuddin et al, 2018;Nurhamidin & Ibrahim, 2018;Rahman et al, 2018;Sanadi et al, 2018;Utami et al, 2018;Lubis et al, 2019;Falah et al, 2020;Lestari et al, 2020;Nawawi et al, 2020;Rahman et al, 2020;Wilda et al, 2020;Hadi et al, 2021;Nursagita & Sulistyaning, 2021;Hilyana et al, 2022). Berdasarkan pemaparan di atas, salah satu alternatif sederhana dalam mendeteksi kontaminasi cemaran limbah logam berat non esensial dari aktivitas pelabuhan Lembar dapat dimulai dengan analisis uji coba kandungan kontaminasi logam berat pada substrat ekosistem mangrove.…”
Section: Pendahuluanunclassified
“…Terjadinya pengurangan jumlah luasan ekosistem mangrove tentunya berdampak pada terjadinya penurunan kualitas kesehatan perairan pelabuhan Lembar dan sekitarnya, sedangkan mangrove sangat berperan penting dalam menopang kehidupan ekonomi dan kesehatan masyarakat pesisir, terutama terhadap cemaran logam berat yang berasal dari aktivitas pelabuhan Lembar. Hal ini didukung oleh berbagai studi terdahulu yang membuktikan bahwa mangrove merupakan salah satu bioakumulator logam berat berbahaya (Nur, 2013;Setiawan, 2013;Analuddin et al, 2017;Nilasari & Wibowo, 2018;Sasnita et al, 2017;Supriyantini et al, 2017;Warni et al, 2017;Khairuddin et al, 2018;Nurhamidin & Ibrahim, 2018;Rahman et al, 2018;Sanadi et al, 2018;Utami et al, 2018;Lubis et al, 2019;Falah et al, 2020;Lestari et al, 2020;Nawawi et al, 2020;Rahman et al, 2020;Wilda et al, 2020;Hadi et al, 2021;Nursagita & Sulistyaning, 2021;Hilyana et al, 2022). Berdasarkan pemaparan di atas, salah satu alternatif sederhana dalam mendeteksi kontaminasi cemaran limbah logam berat non esensial dari aktivitas pelabuhan Lembar dapat dimulai dengan analisis uji coba kandungan kontaminasi logam berat pada substrat ekosistem mangrove.…”
Section: Pendahuluanunclassified
“…This needs to be done because mangrove vegetation plays a role in preventing eutrophication of waters [23]. Besides of that, mangrove vegetation also plays a role in the bioremediation of heavy metals and oil in waters [24][25][26]. With good water quality in the mangrove ecosystem, it will then become a suitable habitat to support the biota within it, including fish.…”
Section: Figmentioning
confidence: 99%
“…In addition, the extensive root structure of R. mucronata is very effective at preventing the entry of sediments and pollutants into the water. Moreover, according to recent studies, the roots of these species have sufficient ability to absorb heavy metals found in waters and sediments (Wilda et al 2020).…”
Section: Mangrove Community Structurementioning
confidence: 99%